THE EFFECT OF AGE ON WOUND HEALING AND PHYSICAL DEVELOPMENT OF LOCAL CATS (Felis catus) POST-OVARIOHYSTERECTOMY SURGERY - Wahyuni, Renji Mailisa; Gunanti, G; Noviana, Deni (Universitas Syiah Kuala, 2023)
The purpose of this study was to evaluate the effect of age on wound healing and physical development of local cats (Felis catus) after ovariohysterectomy. A total of 15 female cats were divided into three age groups (2-4, 5-9, and 10 months old) with each group consisting of five cats. Thetreatment group was sterilized using the lateral flank ovariohysterectomy method. Observations of surgical procedures and physical conditions were carriedout during anesthesia, including onset, duration of anesthesia and surgery, body temperature, heart rate, and respiratory rate. Post-operative observationswere made to evaluate wound healing, hematological profile (RBC, Hb, PCV, WBC, PLT), body weight, Body Condition Score (BCS), bone density, andgrowth plate closure. The results showed that there was no significant difference (P0.05) during anesthesia, wound healing, or an increase in body weight,BCS, and bone density in all age groups. Ovariohysterectomy at 2-4 months old delayed the closure of the bone growth plates (P0.05).Ovariohysterectomy in pubertal and post-pubertal cats is safe to perform as long as good surgical preparation is provided.